Assessment of agricultural information needs in African, Caribbean and Pacific (ACP) States for CTA’s Products and Services: Phase 2: Pacific: Country Report: Solomon Islands - Hoota, Michael; Keqa, Banabas; Peter, Fred (Technical Centre for Agricultural and Rural Cooperation, 2005)
The current study is being initiated and funded by CTA. In the study CTA in collaboration with its regional partners are expected to identify and prioritise agriculture information needs of the Solomon Islands.